2017
DOI: 10.1021/acsmedchemlett.7b00239
|View full text |Cite
|
Sign up to set email alerts
|

Mtb PKNA/PKNB Dual Inhibition Provides Selectivity Advantages for Inhibitor Design To Minimize Host Kinase Interactions

Abstract: Drug resistant tuberculosis (TB) infections are on the rise and antibiotics that inhibit through a novel mechanism could be an important component of evolving TB therapy. Protein kinase A (PknA) and protein kinase B (PknB) are both essential serine-threonine kinases in. Given the extensive knowledge base in kinase inhibition, these enzymes present an interesting opportunity for antimycobacterial drug discovery. This study focused on targeting both PknA and PknB while improving the selectivity window over relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 16 publications
1
53
0
Order By: Relevance
“…screened a diverse library of 1,078 compounds and found a weak non‐selective quinazoline based inhibitor of PknB which was subjected to SAR‐based optimization to yield inhibitors with dual specificity against PknA and PknB. The most potent inhibitor from this study was a 5‐substituted aminopyrimidine which displayed MIC ∼4.7 μM against H37Ra . This potent dual kinase inhibitor was later tested on virulent strain M. tuberculosis H37Rv and was employed to investigate the role of PknA and PknB in regulating diverse cellular functionalities.…”
Section: Inhibitorsmentioning
confidence: 99%
“…screened a diverse library of 1,078 compounds and found a weak non‐selective quinazoline based inhibitor of PknB which was subjected to SAR‐based optimization to yield inhibitors with dual specificity against PknA and PknB. The most potent inhibitor from this study was a 5‐substituted aminopyrimidine which displayed MIC ∼4.7 μM against H37Ra . This potent dual kinase inhibitor was later tested on virulent strain M. tuberculosis H37Rv and was employed to investigate the role of PknA and PknB in regulating diverse cellular functionalities.…”
Section: Inhibitorsmentioning
confidence: 99%
“…Numerous studies have been performed to identify small molecule inhibitors against PknB enzyme from M. tuberculosis . Recently, quinazoline derivatives have been identified that were highly specific and inhibited the kinase activity associated with both PknA and PknB . In addition to PknA and PknB, PknG has also been established as a virulence factor for M. tuberculosis .…”
Section: Screening Approachesmentioning
confidence: 99%
“…Generally, the two regioisomers 2 and 2′ were further converted by nucleophilic substitution reactions and the separation of the regioisomers was carried out in a later step of the reaction sequence. Based on the method of Wang et al., we developed a new protocol leading to compound 2 in 76 % yield with a purity of >98 % after recrystallization from methanol (two times). For a positive outcome of the synthesis, it is essential to work at low temperatures in a polar, nonprotic solvent.…”
Section: Resultsmentioning
confidence: 99%